Female Entrepreneurship a comparison between Mexico, Brasil and Chile - Elizundia, María Eugenia (Estudios de Administración, 2014)
The aim of this study was to analyze female entrepreneurship in Mexico, Brazil, and Chile using data obtained from the Global Entrepreneurship Monitor (GEM) for each country and to analyze,whether any of the key indicators have significant influence in the female entrepreneurial activity, comparing the results with total and male entrepreneurial activity and comparing the results in all three countries. Descriptive analysis and logistic regression was employed. The results show that some of these factors do have a significant influence in female entrepreneurship, that they are the same on comparison with total and male entrepreneurship, and that these factors (except for believing that participants have the required abilities to start a business) are not the same when comparing all three countries. There is still a lack of literature studies on this phenomenon, especially in Latin America. This study attempts to fill this gap.